Exploring the Role of Nutrition and Physiology in Basketball Performance: A Literature Review - Ahmadi Ahmadi; Willadi Rasyid; Wilda Welis; Aldo Naza Putra; Yovhandra Ockta (Postgraduate, University of Mataram, 2024)
This literature review examines the role of nutrition in enhancing physical performance and preventing injuries in military activities. Optimal physical fitness is crucial in military settings, where personnel are regularly exposed to extreme physical demands, including intense training, combat operations, and harsh environmental conditions. Proper nutrition plays a pivotal role in maintaining energy, enhancing muscle recovery, and preventing injuries. Key macronutrients—carbohydrates, proteins, and fats—are essential for sustaining endurance, repairing muscles, and providing steady energy, particularly during prolonged operations. Additionally, micronutrients like vitamins D, calcium, magnesium, and potassium support bone and muscle health, while antioxidants (e.g., vitamins C, E, and zinc) reduce inflammation and accelerate recovery. The review also highlights the significance of hydration and the need for personalized nutrition strategies tailored to the unique demands of military personnel. Studies emphasize that nutrition interventions not only optimize physical performance but also mitigate injury risks and improve recovery, especially in cases of traumatic injuries such as brain trauma. The review suggests that military-specific nutrition guidelines are necessary to enhance readiness and resilience in soldiers. Furthermore, targeted dietary supplementation may help prevent deficiencies and improve overall health. In conclusion, the review underscores the critical role of evidence-based nutrition strategies in maintaining the physical and mental well-being of military personnel, ultimately supporting long-term operational readiness. Further research is recommended to refine these strategies and their application in military contexts